KORELASI PENGGUNAAN GADGET DENGAN PERILAKU BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AL-QURAN HADIS - Nur Fadilah; Siti Zulaikhah; Uswatun Hasanah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
This study aims to analyze the correlation between gadget usage and students’ learning behavior in the Al-Qur’an Hadis subject at MAN 2 Bandar Lampung. The background of this study is grounded in the phenomenon of students low learning behavior and the extensive use of gadgets, which has the potential to disrupt the learning process. The study employed a quantitative approach with a correlational research design. The research population consisted of 321 tenth-grade students, with a sample of 76 students selected using simple random sampling. The research instrument was a non-test questionnaire that had undergone validity and reliability testing, resulting in 30 valid statement items. Data were analyzed using the Product Moment correlation test. The findings reveal a significant positive correlation between gadget usage and students’ learning behavior. Lower levels of appropriate gadget usage (i.e., poorer usage patterns) are associated with poorer learning behavior, and vice versa. The novelty of this study lies in its specific focus on examining the influence of gadget usage on learning behavior within the context of Al-Quran Hadis instruction in a state madrasah, a research area that remains relatively underexplored. These findings contribute theoretically by extending the understanding of how digital technology influences religious learning behavior, while also offering practical implications for teachers, schools, and parents in guiding gadget use in a positive and proportional manner. Furthermore, this study opens opportunities for future research incorporating additional variables such as intrinsic motivation, family support, or digital literacy to enrich learning development strategies in the digital era